ANTHROPOLOGICAL MUTATIONS INDUCED BY THE CONSTRUCTION OF SEBEŞ-TURDA HIGHWAY (PANGEEA, 2025)
Oarda neighborhood is located on the left side of Mureş river, close to the junction with Sebeş river. It is a part of Alba Iulia municipality administration. It is formed from two main parts Down Oarda (Oarda de Jos) and Up Oarda (Oarda de Sus). The layout of the highway Sebeş-Turda begins in Sebeş and follows the river sides of Sebeş river and Mureş river. In Oarda area, the high way gets to the inhabited area close to 15 m. This has a huge impact on people's life style and properties.
Keywords: highway; protecting the population; anthropological mutations; pollution